Rancang Bangun Aplikasi Pengelolaan Sertifikat Digital Berbasis NFT Pada Jaringan Solana - Matthew Imanuel Sumita; Rufman Iman Akbar (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This research aims to design and build a Non-Fungible Token (NFT) based digital certificate management application on the Solana blockchain network. This application enables users to create, verify, and transfer certificates in the form of secure and decentralized non-fungible tokens (NFTs). Testing was conducted in two main aspects: functional and performance. The functional testing results showed a 100% success rate, indicating that all the application's main features performed as expected. In terms of performance, NFT creation took an average of 29 seconds for 0.00008 SOL, NFT verification took 1.5 seconds at no cost, and NFT transfer took 19 seconds at the same cost as creation. These results show that the application is able to perform its functions efficiently and economically on top of the Solana network. This research contributes to the utilization of blockchain technology for transparent and secure digital document management.